Can HbA1c be Used to Screen for Glucose Abnormalities Among Adults with Severe Mental Illness? - Romain, A. J.; Letendre, E.; Akrass, Z.; Avignon, A.; Karelis, A. D.; Sultan, A.; Abdel-Baki, A. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Aim: Prediabetes and type 2 diabetes are highly prevalent among individuals with serious mental illness and increased by antipsychotic medication. Although widely recommended, many obstacles prevent these patients from obtaining a proper screening for dysglycemia. Currently, glycated hemoglobin (HbA1c), fasting glucose, and 2-hour glucose levels from the oral glucose tolerance test are used for screening prediabetes and type 2 diabetes. The objective of this study was to investigate if HbA1c could be used as the only screening test among individuals with serious mental illness.Methods: Cross sectional study comparing the sensitivity of HbA1c, fasting glucose, and 2-h oral glucose tolerance test to detect dysglycemias in serious mental illness participants referred for metabolic complications.Results: A total of 84 participants (43 female; aged: 38.5±12.8 years; BMI: 35.0±6.8 kg/m²) was included. Regarding prediabetes, 44, 44 and 76% were identified by HbA1c, fasting glucose, and 2 h- oral glucose tolerance test respectively and for type 2 diabetes, 60, 53 and 66% were identified by HbA1c, fasting glucose and 2 h-oral glucose tolerance test. The overlap between the 3 markers was low (8% of participants for prediabetes and 26% for Type 2 diabetes). Sensitivity of HbA1c were moderate (range 40–62.5%), while its specificity was excellent (92–93%).Conclusion: The present study indicates a low agreement between HbA1c, fasting glucose and 2-h oral glucose tolerance test. It appears that these markers do not identify the same participants. Thus, HbA1c may not be used alone to detect all glucose abnormalities among individuals with serious mental illness.
Keywords: pre-diabetes; diabetes; obesity; OGTT; fasting glucose; screening